Exploratory Google Trends study of user concerns about oral problems - Aquino-Canchari, Christian Renzo; Caira Chuquineyra, Brenda Sofia (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: More and more people search for health information on the internet and oral health is no exception. Objective: To analyze the changes in the relative volumes of internet searches regarding the most common oral diseases and / or injuries according to the World Health Organization. Methods: Google Trends was used to provide data on the volume of searches on Google for the most common terms of comparison based on diseases and / or oral injuries according to WHO. The period of time chosen was from 2004 to 2019. Five search terms were compared in relation to dental caries, periodontopathies, dental trauma, oral cancer, oral manifestations of HIV, noma, cleft lip and palate, tooth loss, toothache. Results: The search volume measured during the 2004-2019 period, indicated that the comparative terms of higher relative search volumes were: “tooth decay” was the most searched in Jamaica, “gingivitis” in Paraguay, “broken tooth” in the United States, “mouth cancer” in the United Kingdom, “HIV symptoms” in Zimbabwe, “cancrum oris” and “cleft palate” in Ghana, “no teeth” in the United States, “toothache” in Trinidad and Tobago. In the comparison of the five terms of higher relative search volumes in the study, "gingivitis" was the term with the highest relative search volumes. Conclusion: The results obtained confirm the interest in oral diseases and / or injuries through the internet, the search term with the highest frequency of search was "gingivitis", followed by "cleft palate", "tooth decay", "no teeth" and for "broken tooth".